Forms of police violence in the Buenos Aires Province Police at the beginning of the 1960s - Barreneche, Osvaldo (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2012)
This article deals with everyday forms of police violence in the Buenos Aires Province at the beginning of the 1960s. It argues that some illegal practices became part of an institutional way of operating against ordinary crime. These practices also applied against political adversaries, social organizations and individuals protesting against government. Diverse political regimes from the mid 1950s increasingly used and legitimized police force for maintaining what they understood as “order and security.” Some of such practices included arresting without judicial intervention, accusations without evidence, physical and verbal abuses, torture, etc. Consulted primary sources also provide evidences about “debates” within the police regarding their role in accompanying military forces against political enemies as well as common people. The article ended en 1962 when a mature phase of police operations began to apply these “techniques” in killing and disappearing political dissidents such as Felipe Vallese